The drift : a novel - Tudor, C. J. (Ballantine Books, 2023)
"Three ordinary people risk everything for a chance at redemption in this audacious, utterly gripping novel of catastrophe and survival at the end of the world, from the acclaimed author of The Chalk Man. Hannah awakens to carnage, all mangled metal and shattered glass. Evacuated from a secluded boarding school during a snowstorm, her coach careered off the road, trapping her with a handful of survivors. They'll need to work together to escape - with their sanity and secrets intact. Meg awakens to a gentle rocking. She's in a cable car stranded high above snowy mountains, with five strangers and no memory of how they got on board. They are heading to a place known only as "The Retreat," but as the temperature drops and tensions mount, Meg realizes they may not all make it there alive. Carter is gazing out of the window of an isolated ski chalet that he and his companions call home. As their generator begins to waver in the storm, the threat of something lurking in the chalet's depths looms larger, and their fragile bonds will be tested when the power finally fails-for good. The imminent dangers faced by Hannah, Meg, and Carter are each one part of the puzzle. Lurking in their shadows is an even greater threat-one that threatens to consume all of humanity"--